Nonverbal Communication, Interpersonal Relationships, Gestures, Postures, Proxemics. - Sjoraida, Diah Fatma; Nugraha, Aat Ruchiat; Guna, Bucky Wibawa Karya; Ali, Makhrus; Arifin, Andi Harmoko; Nomleni, Anton PW; Hendrik, Hendrik; Pasaribu, Daniel (eScience Humanity Journal, 2024)
This study aims to explore the role of nonverbal communication in interpersonal relationships, with a focus on gestures, postures, and proxemics (physical distance between individuals). Nonverbal communication, which includes body movements, body language, as well as the use of personal space, has a significant impact on the understanding and dynamics of relationships between individuals. The study uses observation and in-depth interview methods to identify patterns of nonverbal communication in daily interactions. The results showed that gestures, postures, and proxemics can affect the way people respond to and understand each other, thereby strengthening or weakening interpersonal relationships. This research contributes to a deeper understanding of the importance of nonverbal elements in building effective and harmonious communication in various social contexts.